ANALISIS EKONOMI KEBIJAKAN DANA DESA TERHADAP KEMISKINAN DESA DI KABUPATEN TULUNGAGUNG - Sari, Intan Mala; Abdullah, Muhammad Faisal (Jurnal Ekonomi Pembangunan, 2017)
The purpose of this research is analysis of the difference rural poverty in district tulungagung between on the 2015 and 2016 and analyze influence of fund village and ADD against rural poverty in Tulungagung district. Analysis tools used twin regression with the panel data to hypothesis testing with F test, t test, and  coefficient of determination () at the error level  . The result of analysis regression panel data with the selected model is Fixed Effect Model that show difference rural poverty in district tulungagung between on the 2015 and 2016, variables used in the model are the village fund and ADD take effect on rural poverty with the every score -4,52 for the village fund and -1,52 for ADD. While the coefficient of determination  () is 0,99 or 99%, variable ability show village fund and ADD explain rural poverty in the tulungagung district is 99%. And influence of fund village and ADD against rural poverty is there any difference at the every village in Tulungagung district.